PÓSTUMAS , SENTIMENTAIS E SATÍRICAS. UM ESTUDO COMPARATIVO ENTRE MACHADO DE ASSIS E OSWALD DE ANDRADE - Rangel, Felipe Reis (2012)
This dissertation aims to make a comparison between the works Memórias Póstumas de Brás Cubas, by Machado de Assis, e Memórias Sentimentais de João Miramar, by Oswald de Andrade. Using the theoretical literature so-called carnavalized, the work analyses these compositional satirical authors in three areas: social, linguistic and narrative, in an attempt to demonstrate how both Memórias used similar principles to denounce and lower the values of bourgeois aristocracy of their respective times. To achieve this literacy dialogism, it is also described the relationship of Machado with the tradition of Menippean satire, especially with Laurence Sterne, and the influences of the historical vanguards on Oswald are also specified